Liquefaction Mitigation Using Lateral Confinement Technique - W. R. Azzam; A. K. Nazir (Advances in Civil Engineering)
The exploration of a series of shaking tests on circular model footing with and without cellular confinement constructed around the footing with variable depths and diameters under the effect of variable net bearing stress is studied. The effect of the confinement on the liquefaction time, final settlement, excess pore water pressure, and induced building acceleration were studied. The consequences showed that installing the cell with minimum diameter closer to footing and sufficient penetration depth significantly delayed the liquefaction time. It can be considered as an alternative technique to decrease both the lateral spreading and the final settlement below the foundation during the shaking. The results demonstrated that the cell reduced the excess pore water pressure within the confined zone and the pore water pressure migration outside the confined block where the liquefaction is induced. Moreover, the peak foundation acceleration of the confined footing soil system is reduced compared with the case of without cell confinement.